Synthesis of Mesoporous ZnO•SiO2 Nanocomposite from Rice Husk for Enhanced Degradation of Organic Substances Including Janus Green B under Visible Light - Nguyen, Thu Huong; Vu, Tuan Cuong; Le, Trung Phong; Nguyen, Thu Huyen; Do, Xuan Truong; Vu, Anh-Tuan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
Rice husk (RH) is often mentioned as an agricultural by-product, often used in the pass as fertilizer and for raw burning. With modern science, RH have been researched and found many new potential benefits and applications. In this study, RH were used to synthesize amorphous SiO2, which was used to prepare the ZnO•SiO2 nanocomposites by a hydrothermal method. The as-synthesized materials were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), and N2 adsorption/desorption isotherm. Their photocatalytic properties were studied by an ultraviolet-vis spectrophotometer and a fluorescence spectrophotometer. The ZnO•SiO2 nanocomposite has an excellent ability to degrade organic substances such as dyes, antibiotics, caffeine, etc. The effects of operating parameters on the photo-degradation reaction progress, including catalyst dosage, initial dye concentration, and pH of the initial dye were investigated in detail. In addition, the photodegradation rate of the dye on the ZnO•SiO2 nanocomposite was evaluated using the pseudo-first-order model. The ZnO•SiO2 nanocomposite can be used as a photocatalyst for wastewater treatment as it detaches much more easily from the solution. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).